2019
DOI: 10.1007/s10072-019-3725-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the SPAST gene causing hereditary spastic paraplegia are related to global topological alterations in brain functional networks

Abstract: Aim Our aim was to describe the rearrangements of the brain activity related to genetic mutations in the SPAST gene. Methods Ten SPG4 patients and ten controls underwent a 5 min resting state magnetoencephalography recording and neurological examination. A beamformer algorithm reconstructed the activity of 90 brain areas. The phase lag index was used to estimate synchrony between brain areas. The minimum spanning tree was used to estimate topological metrics such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…In fact, excessive synchronization reduces the variability of the behaviour of the system, hence narrowing the number of functional states that are readily accessible 27 , 40 . Hypersynchronization and hyperconnected topology have been associated with a variety of neurological diseases 41 , 42 , as well as in preclinical conditions that carry an increased risk of neurodegeneration 43 , hence investigations of the functional repertoires in these diseases and conditions could help characterizing these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, excessive synchronization reduces the variability of the behaviour of the system, hence narrowing the number of functional states that are readily accessible 27 , 40 . Hypersynchronization and hyperconnected topology have been associated with a variety of neurological diseases 41 , 42 , as well as in preclinical conditions that carry an increased risk of neurodegeneration 43 , hence investigations of the functional repertoires in these diseases and conditions could help characterizing these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that clinical motor impairment in HSP is due to more global cerebral impairment than just the motor tracts. A study using magnetoencephalography to assess the connectivity of brain networks found changes that suggested global network rearrangement due to changes beyond motor impairment (54). One study looking at 118 patients with SPG4 HSP found 10% had psychiatric comorbidities and 3.5% had memory impairment, possible reflecting more global cerebral impairment (55).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, excessive synchronization reduces the variability of the behaviour of the system, hence narrowing the number of states that are readily accessible (54,73,74). Hypersynchronization and hyperconnected topology have been associated with a variety of neurological diseases (75,76), as well as in preclinical conditions that carry an increased risk of neurodegeneration (77) hence investigations of the functional repertoires in these diseases and conditions could provide answers to this question.…”
Section: Discussionmentioning
confidence: 99%